Development of Role Playing Based on Traffic Sign Miniature Learning Media in Elementary Schools - Suttrisno, Suttrisno; Shalihah, Fika Rachmatus; Fithriyah, Dewi Niswatul (Indonesian Journal of Education Methods Development, 2025)
General Background: In an era where traffic discipline is increasingly neglected, Specific Background: instilling traffic rule awareness from an early age is critical. The Indonesian subject for grade III elementary students includes material on traffic signs. Knowledge Gap: However, conventional teaching methods relying on lectures and textbooks often lead to student disengagement, especially when interpreting symbolic traffic signs. Aims: This study aims to develop a role-playing-based miniature traffic sign learning media to enhance student comprehension and engagement. Results: Utilizing the ADDIE Research and Development model, product validation involved media, material, and language experts, as well as students. Validation results showed scores of 90% (media), 88.5% (material), and 90% (language), while student responses reached 96%, all categorized as "Very Feasible". Student learning outcomes also improved significantly, with pretest and posttest averages rising from 52.5 to 80.5. Novelty: This media integrates hands-on, interactive learning with role-play to bridge cognitive challenges in understanding abstract symbols. Implications: The findings suggest that such innovative media can substantially increase student motivation and achievement, offering a replicable model for similar educational challenges. Highlights: Increases student engagement through interactive role-play. Significantly improves learning outcomes on traffic sign material. Validated as highly feasible by experts and student responses. Keywords: Learning Media, Role-Playing, Traffic Signs, Elementary Education, Indonesian Language